Frankliniella intonsa (Trybom), a thrips species infesting strawberry in La Trinidad, Benguet Province, Philippines - Mintu, Cynthia B. (Animo Repository, 2018)
La Trinidad (Benguet Province, Philippines) is the most established commercial strawberry growing area in the Philippines. The study aimed to identify thrips associated with strawberry at the Balili Experimental Area of Benguet State University in La Trinidad, and to correlate population of thrips with temperature. This study also aimed to investigate the unconfirmed report that Frankliniella occidentalis (Pergande), a vector of strawberry necrotic shock virus in the USA, Israel and Australia, invaded the area. Strawberry var Sweet Charlie was planted in seven plots of approximately 200 m. sq. each, and field preparation, fertilizer application, planting method, mulching and buffering followed the prescribed procedure for planting strawberry in the experimental site. Sampling was done weekly for six weeks from March 10 to April 14, 2018 when the plants were in the flowering stage. Five leaves and flowers of strawberry were collected from each plot and taken as samples, and representative thrips specimens were sorted under Olympus CX33 stereomicroscope, preserved in ethanol, cleared, and mounted on slides using Canada balsam and examined under Nikon CiL research microscope. Findings showed that Frankliniella intonsa (Trybom) was the only species of thrips infesting strawberry in the study site. Females were more numerous than males and larvae, respectively. F. intonsa is an invasive, Eurasian flower thrips that are known as pest of strawberry in Indonesia, Italy and United Kingdom. The polyphagous insect pest is also known to transmit tomato spotted wilt virus, tomato chlorotic spot virus, groundnut ringspot virus, and Impatiens necrotic spot virus in other countries. Moreover, there was a significant linear relationship between thrips population on strawberry and temperature over the range of 23 to 25.6°C. Since Benguet Province grows ornamental plants, tomato and other high value crops, surveillance and monitoring of the build up of F. intonsa population on strawberry during the summer months is recommended. © Rushing Water Publishers Ltd. 2018.